Untersuchung des Erreichbarkeitsproblems in ungerichteten Graphen bezüglich den Komplexitätsklassen L und SL - Biermeier, Felix

Evaluierung von Initialisierungsmethoden für Fuzzy-k-means Algorithmen - Sauer, Malte

Erwerb von Handlungskompetenz in Communities of Practice - Bloh, Thiemo

Zur Bedeutung Anderer bei der Entwicklung von Expertise – Eine Analyse berufsbiographischer Narrationen von Grundschullehrkräften - Bloh, Thiemo

Korrosionsuntersuchungen an experimentellen und technisch relevanten Magnesiumlegierungen - Hoyer, Kay-Peter

Rainbow connection number of graph power and graph products - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

Rainbow connection number and radius - Basavaraju, Manu; Chandran, L Sunil; Rajendraprasad, Deepak; Ramaswamy, Arunselvan (Graphs and Combinatorics)

The setting behavior of dispersion adhesives during bonding of Wood Plastic Composites (WPC) - Moritzer, Elmar; Hopp, Matthias (67th Annual Assembly of the International Institute of Welding (IIW))

The same but not the same - Challenges in comparing patient opinions - Geierhos, Michaela; Schulze, Sabine

What is research ethics observing? An interdisciplinary {\ "a} re discussion between computational linguistics and qualitative-constructivist social research} - Geierhos, Michaela; Siri, Jasmin (Proceedings Research Ethics in Qualitative and Quantitative Social Research)

Ans {\ "a} sets for ü r an online optimization of the lot sizes in the Series production - Dangelmaier, Wilhelm

Modeling of the PLC Behavior in Intralogistics with Non-Autonomous Hybrid Petri-Nets - Kopecki, Lukas; Lauck, Sebastian

Information Systems for Composite Materials: Requirements and Challenges - Dangelmaier, Wilhelm; Sommer-Dittrich, Thomas; Streichhan, Jenny; Monhof, Markus (Applied Mechanics and Materials)

Comparative study on disambiguating acronyms in the scientific papers using the open knowledge base - Jeong, Do-Heon; Gim, Jangwon; Jung, Hanmin; Geierhos, Michaela; Baeumer, Frederik Simon (Proceedings of the 9th Asia Pacific International Conference on Information Science and Technology)

An Evolutionary Approach on Multi-objective Scheduling for Evolving Manufacturing Systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 47th Annual Hawaii International Conference on System Sciences)
New paradigms for designing manufacturing systems, such as adaptive and service-oriented manufacturing systems or self-optimizing resources, introduce new degrees of freedom into manufacturing control. These paradigms lead to the research question how human decision makers can be enabled to exploit the high adaptability of the new manufacturing systems in accordance to the current requirements arising from quickly changing market requirements and demand for sustainable manufacturing. This contribution extends a scheduling model for self-optimizing and service-oriented manufacturing systems through the consideration of alternative resources and introduces a multi-objective scheduling concept based on evolutionary algorithms in combination with a new optimized type of crossover operator.

Acceleration of Materialflow Simulations Using Model Coarsening by Token Sampling and Online Error Estimation and Accumulation Controlling - Renken, Hendrik

Towards a Local Grammar-based Persondata Generator for Wikipedia Biographies - Geierhos, Michaela (Penser le Lexique-Grammaire)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Bright integrated photon-pair source for practical passive decoy-state quantum key distribution - Krapick, S.; Stefszky, Michael; Jachura, M.; Brecht, Benjamin; Avenhaus, M.; Silberhorn, Christine (Physical Review A)

Absence of pressure sensitivity of apparent wall slip in pressure-driven flow of non-colloidal suspensions - Pieper, Sven; Kirchhoff, Nadine; Schmid, Hans-Joachim (Rheologica Acta)
We investigated an explanation for the length dependence of apparent wall slip in capillary and slit die experiments that had been implied in earlier studies. Firstly, we used a very long slit die fitted with six equidistant pressure transducers and an adjustable outlet. It was found that, all other parameters being equal, the impact of pressure on the flow behavior of suspensions was not different from the impact on the unfilled matrix fluid. Particle-related properties, such as apparent wall slip, were therefore not influenced by pressure as assumed by other authors. Secondly, we determined wall slip velocities by both the Mooney method and numerical simulation, based on an implementation of Phillips constitutive equation for particle migration. This led to a similar length dependence of wall slip as had been reported in an earlier work. We concluded that this was due to the transient nature of particle migration and its interrelationship with apparent wall slip, rather than an influence of pressure.

Ultrafine Dust Filtration Using Precoat Materials Considering the Influence of Filter Media - Schiller, Sascha; Schmid, Hans-Joachim (Chemical Engineering & Technology)
Ultrafine dust separation from different sources like industry, traffic, or private households has become increasingly important in the last decade. A compact baghouse filter system has been developed which is suitable for pellet heaters. For filtration, a precoat material is required to prevent clogging of the filter media by the ultrafine dust particles. In order to ensure the best performance of this filter system, different combinations of filter media and precoat materials, e.g., grade efficiencies and the cake area load for the various filter media, were investigated in a special test rig. With this highly efficient technology, extremely high separation efficiencies of > 99 % and ultrafine dust concentrations of > 1 mg cm−3 could be reached in a long-term stable process.

Simulation of Capillary Bridges between Nanoscale Particles - Dörmann, Michael; Schmid, Hans-Joachim (Langmuir)
Capillary forces are very important as they exceed in general other adhesion forces. But at the same time the exact calculation of these forces is very complex, so often assumptions and approximations are used. Previous research was done with regard to micrometer sized particles, but the behavior of nanoscale particles is different. Hence, the results for micrometer sized particles cannot be directly transferred when considering nanoscale particles. Therefore, a simulation method was developed to calculate numerically the shape of a rotationally symmetrical capillary bridge between two spherical particles or a particle and a plate. The capillary bridge in the gap between the particles is formed due to capillary condensation and is in thermodynamic equilibrium with the gas phase. Hence the Kelvin equation and the Young–Laplace equation can be used to calculate the profile of the capillary bridge, depending on the relative humidity of the surrounding air. The bridge profile consists of several elements that are determined consecutively and interpolated linearly. After the shape is determined, the volume and force, divided into capillary pressure force and surface tension force, can be calculated. The validation of this numerical model will be shown by comparison with several different analytical calculations for micrometer-sized particles. Furthermore, it is demonstrated that two often used approximations, (1) the toroidal approximation and (2) the use of an effective radius, cannot be used for nanoscale particles without remarkable mistake. It will be discussed how the capillary force and its components depend on different parameters, like particle size, relative humidity, contact angle, and distance, respectively. The rupture of a capillary bridge due to particle separation will also be presented.

Outsourcing von Lagerdienstleistungen als operatives Entscheidungsproblem - Betz, Stefan (Logistikorientiertes Produktionsmanagement)

Verfahren zur Entwicklung geschäftsmodellorientierter Diversifikationsstrategien - Lehner, Markus

Systematik für die integrative Konzipierung der Montage auf Basis der Prinziplösung mechatronischer Systeme - Brandis, Rinje

Systematik zur Entwicklung von Geschäftsmodellen in der Produktentstehung - Köster, Oliver

Rahmenwerk zur Modellierung einer plausiblen Systemstruktur mechatronischer Systeme - Kaiser, Lydia

Systematik zur Planung von CrossIndustry-Innovationen - Echterhoff, Niklas

A Design Framework for Developing a Reconfigurable Driving Simulator - Hassan, Bassem

Model Consistency Management for Systems Engineering - Rieke, Jan

Beating Irrationality: Does Delegating to IT Alleviate the Sunk Cost Effect? - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Management Science)

Systematik der virtuellen Inbetriebnahme von automatisierten Produktionssystemen - Brökelmann, Jan

Using Income Accounting as the Theoretical Basis for Measuring IT Productivity - Kundisch, Dennis; Mittal, Neeraj; Nault, Barrie (Information Systems Research)

Don't take away my Status! - Evidence from the Restructuring of a Virtual Reward System - Mutter, Tobias; Kundisch, Dennis (Computer Networks)

Business Models - An Information Systems Research Agenda - Veit, Daniel; Clemons, Eric; Benlian, Alexander; Buxmann, Peter; Hess, Thomas; Kundisch, Dennis; Leimeister, Jan-Marco; Loos, Peter; Spann, Martin (Business & Information Systems Engineering)

Geschäftsmodelle - Eine Forschungsagenda für die Wirtschaftsinformatik - Veit, D.; Clemons, E.; Buxmann, A.; Hess, T.; Kundisch, Dennis; Leimeister, J.-M.; Loos, P.; Spann, M. (Wirtschaftsinformatik)

Analyzing Cost and Risk Interaction Effects in IT Project Portfolios - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (BIT - Banking and Information Technology)

Structural Quantification of Entanglement - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review Letters)

Detection of nonlocal superpositions - Gutiérrez-Esparza, A. J.; Pimenta, W. M.; Marques, B.; Matoso, A. A.; Sperling, Jan; Vogel, W.; Pádua, S. (Physical Review A)

Witnessing the degree of nonclassicality of light - Mraz, M.; Sperling, Jan; Vogel, W.; Hage, B. (Physical Review A)

Unified quantification of nonclassicality and entanglement - Vogel, W.; Sperling, Jan (Physical Review A)

Quantum state engineering by click counting - Sperling, Jan; Vogel, W.; Agarwal, G. S. (Physical Review A)

Bipartite bound entanglement in continuous variables through degaussification - Steinhoff, F. E. S.; de Oliveira, M. C.; Sperling, Jan; Vogel, W. (Physical Review A)

Operational Gaussian Schmidt-number witnesses - Shahandeh, F.; Sperling, Jan; Vogel, W. (Physical Review A)

Kollektive Orientierungsmuster als Teil individueller Handlungskompetenz: Eine komparative Analyse kooperierender Grundschullehrkräfte - Bloh, Thiemo (Perspektiven auf inklusive Bildung)

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, T (Nonlinearity)

Formation and interaction of resonance chains in the open three-disk system - Weich, T; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)

Spectral properties of microwave graphs with local absorption - Allgaier, Markus; Gehler, Stefan; Barkhofen, Sonja; Stöckmann, H.-J.; Kuhl, Ulrich (Physical Review E)

Twenty years of learning with the World Wide Web - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix
n the summer of 1994, courses at universities were supported for the first time through the use of the World Wide Web. With the introduction of this new technology, high expectations quickly arose that the established forms of teaching and learning in schools and universities would be replaced and that the institutions themselves might even prove to be superfluous. Twenty years later, it turns out that there is a great gap between hope and reality. Some of the ideas at the time that, for example, having access to the world's knowledge at any time would make textbooks superfluous, turned out to be naive in retrospect. Characteristic of the ideas at that time was the assumption that didactic and organizational problems of teaching and learning could be solved purely technically.

Zwischen Design und Flexibilität - Zur Ergonomie des Flat Design - Winkelnkemper, Felix; Keil, Reinhard

Forschendes Lernen durch semantisches Positionieren - Jakoblew , Marcel; Keil, Reinhard; Winkelnkemper, Felix (Proceedings der HDI 2014)

Hypothesengeleitete Gestaltung von Benutzungsoberflächen - Keil, Reinhard; Schild, Christian

Knowledge integration processes and distributed knowledge organization - Keil, Reinhard

Erklärungsfaktoren für Einstellungen von Lehrerinnen und Lehrern zum inklusiven Unterricht in der Grundschule - Hellmich, Frank; Görel, Gamze (Zeitschrift für Bildungsforschung)

Einstellungen zur Inklusion und Vorerfahrungen aus dem „Gemeinsamen Unterricht“ bei Lehrkräften in der Grundschule - Hellmich, Frank; Görel, Gamze (Forschung zu inklusiver Bildung. Gemeinsam anders lehren und lernen)

Wahrnehmung von Rückmeldungen durch Kinder im Leseunterricht der Grundschule im Zusammenhang mit ihrem Leseverständnis und ihren selbstbezogenen Kognitionen und Motivationen. - Hellmich, Frank; Hoya, Fabian Karl (Empirische Bildungsforschung und evidenzbasierte Reformen im Bildungswesen)

Individuelles Feedback in heterogen zusammengesetzten Lerngruppen im Leseunterricht der Grundschule – Befunde aus einer empirischen Studie - Hoya, Fabian Karl; Hellmich, Frank (Perspektiven auf inklusive Bildung)

Die Rolle von Klassenklima und Rückmeldungen für Selbstkonzept, Motivation und Leseleistung bei Kindern im Grundschulunterricht – Ergebnisse aus einer empirischen Studie - Hellmich, Frank; Hoya, Fabian Karl (Beziehungen in Schule und Unterricht (Teil 2). Soziokulturelle und schulische Einflüsse auf pädagogische Beziehungen)

Die Rolle von Klassenklima und Rückmeldungen für Selbstkonzept, Motivation und Leseleistung bei Kindern im Grundschulunterricht – Ergebnisse aus einer empirischen Studie - Hellmich, Frank; Hoya, Fabian Karl (Schulpädagogik-heute)

Lesefähigkeiten und metakognitive Lesestrategien bei Kindern mit Deutsch als Erst- und Zweitsprache im Vergleich - Hellmich, Frank; Niebuhr-Siebert, Sandra; Förster, Sabrina (Individuelle Förderung und Lernen in der Gemeinschaft)

Kleinräumige lebenslagenbezogene kommunale Sozialberichterstattung für die Stadt Guben - Meier-Gräwe, Uta; Klünder, Nina; Pathenschneider, Mira

Prospective relevance of dietary patterns at the beginning and during the course of primary school to the development of body composition - Diethelm, Katharina; Günther, Anke L. B.; Schulze, Matthias B.; Standl, Marie; Heinrich, Joachim; Buyken, Anette (British Journal of Nutrition)
Primary school years seem to represent a critical period for the development of overweight and obesity. However, only a few studies have analysed the prospective relationship between dietary patterns and weight status in children. The aims of the present study were to identify dietary patterns at the beginning of and during the primary school period and to examine their relevance to the development of body composition. Nutritional and anthropometric data from 371 participants of the Dortmund Nutritional and Longitudinally Designed (DONALD) Study at the beginning (ages 6 and 7 years) and end (ages 10 and 11 years) of the primary school period were used. Principal component analyses (PCA) were conducted to identify dietary patterns, which were regressed on changes in BMI and fat mass index (FMI) between ages 6 and 7 years and ages 10 and 11 years. Reduced rank regression (RRR) was used to directly extract patterns explaining variation in changes in BMI and FMI between ages 6 and 7 years and ages 10 and 11 years. PCA yielded interpretable patterns of dietary changes at the beginning of and during the primary school period, which were not related to changes in body composition. Conversely, RRR allowed identifying predictive patterns: higher baseline intakes of white bread and lower baseline intakes of whole-grain products as well as increases in the consumption of savoury snacks, sausages and cheese during primary school years independently predicted increases in BMI and FMI during the primary school period. In conclusion, selection of unfavourable carbohydrate sources at the beginning of the primary school period and increases in the consumption of processed savoury foods during primary school years may adversely affect the development of body composition during the course of primary school.

Dietary glycemic load, insulin load, and weight loss in obese, insulin resistant adolescents: RESIST study - Joslowski, Gesa; Halim, Jocelyn; Goletzke, Janina; Gow, Megan; Ho, Mandy; Louie, Jimmy C.-Y.; Buyken, Anette; Cowell, Chris T.; Garnett, Sarah P. (Clinical Nutrition)

Association between carbohydrate quality and inflammatory markers: systematic review of observational and interventional studies - Buyken, Anette; Goletzke, Janina; Joslowski, Gesa; Felbick, Anna; Cheng, Guo; Herder, Christian; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

Velocities of weight, height and fat mass gain during potentially critical periods of growth are decisive for adult body composition - Cheng, G; Bolzenius, K; Joslowski, G; Günther, A L B; Kroke, A; Heinrich, J; Buyken, Anette (European Journal of Clinical Nutrition)

Increased Intake of Carbohydrates from Sources with a Higher Glycemic Index and Lower Consumption of Whole Grains during Puberty Are Prospectively Associated with Higher IL-6 Concentrations in Younger Adulthood among Healthy Individuals - Goletzke, Janina; Buyken, Anette; Joslowski, Gesa; Bolzenius, Katja; Remer, Thomas; Carstensen, Maren; Egert, Sarah; Nöthlings, Ute; Rathmann, Wolfgang; Roden, Michael; Herder, Christian (The Journal of Nutrition)

Low Carbon Economics - Theory and application - Gries, Thomas (Low Carbon Economics)

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Zur Ausbreitung und Behinderung von Epidemien - Eine Netzwerkanalyse - Drigalsky, Liesa

Webcam application using virtual FPGA - Wu, Sen

Was tun um Kunden von der Qualität seiner Produkte zu überzeugen - Möglichkeiten der Zertifizierung und von Reputationssystemen auf Onlinemärkten - Lange, Maximilian

Visualisierung von SMT-Solver-Ausgaben - Osterbrink, Sebastian

Vertical Thread Migration in FPGA based Sound Localization - Wagener, Peter

Verified Service Compositions by Template-Based Construction - Walther, Sven; Wehrheim, Heike (Proceedings of the 11th International Symposium on Formal Aspects of Component Software (FACS))
Today, service compositions often need to be assembled or changed on-the-fly, which leaves only little time for quality assurance. Moreover, quality assurance is complicated by service providers only giving information on their services in terms of domain specific concepts with only limited semantic meaning. In this paper, we propose a method to construct service compositions based on pre-verifiedtemplates. Templates, given as workflow descriptions, are typed over a (domain-independent) template ontology defining concepts and predicates. Templates are proven correct using an abstract semantics, leaving the specific meaning of ontology concepts open, however, only up to given ontology rules. Construction of service compositions amounts to instantiation of templates with domain-specific services.Correctness of an instantiation can then simply be checked by verifying that the domain ontology(a) adheres to the rules of the template ontology, and (b) fulfills the constraints of the employed template.

Verhandlungen vs Auktionen im Beschäftigungsmanagement - Berkemeier, Christopher

Verhandlungen bei variablem status quo: Eine Modifikation des Adjustet Winner Verfahrens - Beck, Henri

Finanzierung - Grundlagen, Institutionen, Instrumente und Kapitalmarkttheorie - Gräfer, Horst; Schiller, Bettina; Rösner, Sabrina
Dieses Lehr- und Arbeitsbuch präsentiert Ihnen die wichtigsten Grundlagen der Unternehmensfinanzierung auf dem neuesten fachlichen Stand. Der perfekte Einstieg in ein zentrales finanzwirtschaftliches Fach- und Praxisgebiet – mit vielen Beispielen und Übungen.
Keywords: Management; Wirtschaft

Using Application Layer Knowledge in Routing and Wavelength Assignment Algorithms - Wette, Philip; Karl, Holger (Proceedings of the IEEE International Conference on Communications 2014)
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case notenough resources are available to set up a new lightpath in aWavelength Division Multiplexing (WDM) network. The selectionof lightpaths to be preempted relies on internal decisions of theRWA algorithm. Thus, if dedicated properties of the networktopology are required by the applications running on the network,these requirements have to be known to the RWA algorithm.We present a family of preemptive RWA algorithms for WDMnetworks. These algorithms have two distinguishing features: a)they can handle dynamic traffic by on-the-fly reconfiguration,and b) users can give feedback for reconfiguration decisions andthus influence the preemption decision of the RWA algorithm,leading to networks which adapt directly to application needs.This is different from traffic engineering where the network is(slowly) adapted to observed traffic patterns.Our algorithms handle various WDM network configurationsincluding networks consisting of heterogeneous WDM hardware.To this end, we are using the layered graph approach togetherwith a newly developed graph model that is used to determineconflicting lightpaths.

Untersuchung transitiver Eigenschaften der Technik "Programs from Proofs" - Korth, Philipp

Two-Sided Market and Game Console Vendors - Fang Cheng, Terry

Transformation graphischer Protokollspezifikationen in Model-Checker-Anfragen - Klauke, Christoph

Tragedy of the Common Cloud - Game Theory on the Infrastructure-as-a-Service Market - Künsemöller, Jörn

IT-basierte Dienstleistungen für die Elektromobilität --- Konzeptioneller Rahmen und Literaturanalyse - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Matzner, Martin (Proceedings of the Multikonferenz Wirtschaftsinformatik 2014 (MKWI 2014))

Towards Systematic Configuration for Architecture Validation - Becker, Matthias; Becker, Steffen; Besova, Galina; Walther, Sven; Wehrheim, Heike (Proceedings of the 40th Euromicro Conference on Software Engineering and Advanced Applications (Work in Progress Session))

Towards Context-Sensitive Service Composition for Service-Oriented Image Processing - Jungmann, Alexander; Kleinjohann, Bernd (Proceedings of the 6th International Conference on Cloud Computing Technology and Science (CloudCom))
Automatically composing service-based software solutions is a challenging task. Considering context information during this service composition process is even more challenging. In domains such as image processing, however, context-sensitivity is inherent and cannot be ignored when developing techniques for automatic service composition. Formal approaches tend to create ambiguous solutions, whenever the expressive power of the applied formalism is limited. For example, services may have the same formal specification, although their actual functionality depends on the concrete context. In order to satisfy individual user requests while providing data-dependent functionality, formal approaches have to be extended. We propose to incorporate Reinforcement Learning techniques and combine them with planning based composition approaches. While planning ensures formally correct solutions, learning enables the composition process to resolve ambiguity by implicitly considering context information. Preliminary results show that our combined approach adapts to a static context while still satisfying formally specified requirements.

Towards a Flexible and Privacy-Preserving Reputation System for Markets of Composed Services - Brangewitz, Sonja; Jungmann, Alexander; Petrlic, Ronald; Platenius, Marie Christin (Proceedings of the 6th International Conferences on Advanced Service Computing (SERVICE COMPUTATION))
One future goal of service-oriented computing is to realize global markets of composed services. On such markets, service providers offer services that can be flexibly combined with each other. However, most often, market participants are not able to individually estimate the quality of traded services in advance. As a consequence, even potentially profitable transactions between customers and providers might not take place. In the worst case, this can induce a market failure. To overcome this problem, we propose the incorporation of reputation information as an indicator for expected service quality. We address On-The-Fly Computing as a representative environment of markets of composed services. In this environment, customers provide feedback on transactions. We present a conceptual design of a reputation system which collects and processes user feedback, and provides it to participants in the market. Our contribution includes the identification of requirements for such a reputation system from a technical and an economic perspective. Based on these requirements, we propose a flexible solution that facilitates the incorporation of reputation information into markets of composed services while simultaneously preserving privacy of customers who provide feedback. The requirements we formulate in this paper have just been partially met in literature. An integrated approach, however, has not been addressed yet.

Thread Shadowing: Using Dynamic Redundancy on Hybrid Multi-cores for Error Detection - Meisner, Sebastian; Platzner, Marco (Proceedings of the 10th International Symposium on Applied Reconfigurable Computing (ARC))
Dynamic thread duplication is a known redundancy technique for multi-cores. The approach duplicates a thread under observation for some time period and compares the signatures of the two threads to detect errors. Hybrid multi-cores, typically implemented on platform FPGAs, enable the unique option of running the thread under observation and its copy in different modalities, i.e., software and hardware. We denote our dynamic redundancy technique on hybrid multi-cores as thread shadowing. In this paper we present the concept of thread shadowing and an implementation on a multi-threaded hybrid multi-core architecture. We report on experiments with a block-processing application and demonstrate the overheads, detection latencies and coverage for a range of thread shadowing modes. The results show that trans-modal thread shadowing, although bearing long detection latencies, offers attractive coverage at a low overhead.

The Xilinx Zynq Architecture as a Platform for Reconfigurable Heterogeneous Multi-Cores - Rüthing, Christoph

The Legal Classification of Identity-Based Signatures - Sorge, Christoph
Identity-based cryptography has attracted attention in the cryptographic research communityin recent years. Despite the importance of cryptographic schemes for applicationsin business and law, the legal implications of identity-based cryptography have not yetbeen discussed. We investigate how identity-based signatures fit into the legal framework.We focus on the European Signature Directive, but also take the UNCITRAL Model Law onElectronic Signatures into account. In contrast to previous assumptions, identity-basedsignature schemes can, in principle, be used even for qualified electronic signatures,which can replace handwritten signatures in the member states of the European Union.We derive requirements to be taken into account in the development of future identitybasedsignature schemes.

On the Ontological Expressiveness of Conceptual Modeling Grammars for Service Productivity Management - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Peter Rauer, Hans; Sigge, Daniel (Information Systems and e-Business Management)

Exploring the Interplay of the Design and Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Business and Information Systems Engineering)

Über das Zusammenwirken der Gestaltung und Emergenz von Geschäftsprozessen als Organisationsroutinen - Beverungen, Daniel (WIRTSCHAFTSINFORMATIK)

The Interaction of Signals: A Fuzzy set Analysis of the Video Game Industry - Kaimann, Daniel; Cox, Joe
Customers continuously evaluate the credibility and reliability of a range of signals both separately and jointly. However, existing econometric studies pay insufficient attention to the interactions and complex combinations of these signals, and are typically limited as a result of difficulties controlling for multicollinearity and endogeneity in their data. We develop a novel theoretical approach to address these issues and study different signaling effects (i.e., word-of-mouth, brand reputation, and distribution strategy) on customer perceptions. Using data on the US video games market, we apply a fuzzy set qualitative comparative analysis (fsQCA) to account for cause-effect relationships. The results of our study address a number of key issues in the economics and management literature. First, our results support the contention that reviews from professional critics act as a signal of product quality and therefore positively influence unit sales, as do the discriminatory effects of prices and restricted age ratings. Second, we find evidence to support the use of brand extension strategies as marketing tools that create spillover effects and support the launch of new products.

The Impact of Customer Reviews and Reputation on Hotel Prices - Holzweißig, Lena

The Economics of Individual Behavior in Competitive Environments: Empirical Evidence from Real-Life Tournaments - Scheel, Friedrich

Template-based Generation of Semantic Services - Mohr, Felix; Walther, Sven (Proceedings of the 14th International Conference on Software Reuse (ICSR))
There are many technologies for the automation of processesthat deal with services; examples are service discovery and composition.Automation of these processes requires that the services are described semantically. However, semantically described services are currently not oronly rarely available, which limits the applicability of discovery and composition approaches. The systematic support for creating new semanticservices usable by automated technologies is an open problem.We tackle this problem with a template based approach: Domain independent templates are instantiated with domain specific services andboolean expressions. The obtained services have semantic descriptionswhose correctness directly follows from the correctness of the template.Besides the theory, we present experimental results for a service repository in which 85% of the services were generated automatically.

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Template Embedding: Using Application Architecture to Allocate Resources in Distributed Clouds - Keller, Matthias; Robbert, Christoph; Karl, Holger (Proceedings of 7th International Conference on Utility and Cloud Computing (UCC))
In distributed cloud computing, application deployment across multiple sites can improve quality of service. Recent research developed algorithms to find optimal locations for virtual machines. However, those algorithms assume to have either single-tier applications or a fixed number of virtual machines – a strong simplification of reality. This paper investigates the placement and scaling of complex application architectures. An application is dynamically scaled to fit both the current demand situation and the currently available infrastructure resources. We compare two approaches: The first one is based on virtual network embedding. The second approach is a novel method called Template Embedding. It is based on a hierarchical 1-allocation hub flow problem and combines applica- tion scaling and embedding in one step. Extensive experiments on 43200 network configurations showed that Template Embedding outperforms virtual network embedding in all cases in three metrics: success rate, solution quality, and runtime. This positive result shows that template embedding is a promising approach for distributed cloud resource allocation.

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Tampering attacks in pairing-based cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Proceedings of Fault Tolerance and Diagnosis in Cryptography(FDTC))
In the last decade pairings have become an important, and often indispensable, ingredient in the construction of identity-based and attribute-based cryptosystems, as well as group signatures and credential systems. Consequently, the applicability of timing, power, or fault attacks to implementations of pairings is an important research topic. We will review some of the known results in this area.